Validation of CCAFS Outcomes for CIAT in the Philippines - Adaro, Catharine E (2019)
This report documents the validation activity to verify the nature of identified CCAFS outcomes for CIAT in the Philippines covering the period of 2016 up to present. Specifically, the validation assessed the changes in Knowledge, Attitude, Skills and Practices (KAS+P) of institutional intermediate users related to the following outcomes identified by CIAT: 1) the use of outputs of CIAT collaborative climate research in the planning and establishing of CRA/AMIA villages; 2) the use of CIAT collaborative climate research for formulating policy frameworks and plans for national agricultural development agenda and services.; and 3) the use of outputs from CIAT collaborative climate research to inform the DA proposal for GCF on scaling up climate-resilient agriculture and fisheries in the Philippines.